A Genome-wide Analysis Identifies Genetic Variants in the RELN Gene Associated with Otosclerosis - Schrauwen, Isabelle (American Society of Human Genetics, 2009)
Otosclerosis is a common form of progressive hearing loss, characterized by abnormal bone remodeling in the otic capsule. The etiology of the disease is largely unknown, and both environmental and genetic factors have been implicated. To identify genetic factors involved in otosclerosis, we used a case-control discovery group to complete a genome-wide association (GWA) study with 555,000 single-nucleotide polymorphisms (SNPs), utilizing pooled DNA samples. By individual genotyping of the top 250 SNPs in a stepwise strategy, we were able to identify two highly associated SNPs that replicated in two additional independent populations. We then genotyped 79 tagSNPs to fine map the two genomic regions defined by the associated SNPs. The region with the strongest association signal, p(combined) = 6.23 × 10(−10), is on chromosome 7q22.1 and spans intron 1 to intron 4 of reelin (RELN), a gene known for its role in neuronal migration. Evidence for allelic heterogeneity was found in this region. Consistent with the GWA data, expression of RELN was confirmed in the inner ear and in stapes footplate specimens. In conclusion, we provide evidence that implicates RELN in the pathogenesis of otosclerosis.